The evolution of new ventures’ behavioral strategies and the role played by governments in the green entrepreneurship context: an evolutionary game theory perspective - Yang, Xu; Liao, Shan; Li, Runmao (Environmental science and pollution research international, 2021)
Green entrepreneurship is a special type of entrepreneurship that can achieve sustainable development, which is advocated for by many countries and regions. Accordingly, large-scale green entrepreneurship activities of new ventures are appearing in the emerging green industry around the world. To initially study how to promote the diffusion of eco-innovation in green entrepreneurship activities, the evolutionary game models of new ventures’ eco-innovation and greenwashing behavior affected by market mechanisms and government regulations were respectively established. Furthermore, a benign evolution path of the system was proposed by analyzing the evolutionary stable state of the green entrepreneurial system composed of the government and new ventures. Then, the simulation analysis was carried out using a case study to more intuitively observe the influence of some important parameters including government subsidies and so forth on the evolutionary stable state of the system. The research showed that it is difficult for pure market mechanisms to promote the spread of new ventures’ eco-innovation behaviors in the initial stage of the development of the emerging green industry, and the government regulation is exceedingly important. The parallel use and timely adjustments between the government subsidy and penalty mechanisms can effectively promote the diffusion of new ventures’ eco-innovation behaviors under certain conditions. Besides, the size (positive and negative) of the benefits gaps realized by “greenwashing” and “eco-innovation” radically determines the direction and result of the evolution of new ventures’ behavioral strategies.